Nanostructure and magnetostriction in novel discontinuous terfecohan/YFe Exchange-spring type multilayers - Do, Giang Thi Huong; Nguyen, Duc Huu; Pham, Thuong Thi (VNU Journal of Science: Mathematics - Physics; Vol 20 No 2, 2017)
Abstracts